Flower Pollination for Rotary Inverted Pendulum Stabilization with Delay - Srikanth Kavirayani; Nagesh Kumar Gundavarapu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
Flower pollination is a single objective optimization technique which as a unconstrained optimization method is applied for the stabilization of the rotary inverted pendulum system. It was observed that the flower pollination method gave better sensitivity in control of the pendulum about its upright unstable equilibrium position with less time and definitely indicated that the method is an energy efficient method when compared with other methods like direct pole placement.  This method yielded results under the influence of time delay and have proven that the influence of time delay is significantly felt and would cause loss of energy, however the presence of flower pollination for optimization minimizes the loss incurred due to time delay and makes the system significant in terms of sensitivity.